Experimental Investigation on an Absorption Refrigerator Driven by Solar Cells. (12th February 2013) - Chien, Zi-Jie; Cho, Hung-Pin; Jwo, Ching-Song; Chien, Chao-Chun; Chen, Sih-Li; Chen, Yen-Lin
Abstract : This experiment is to study an absorption refrigerator driven by solar cells. Hand-held or carried in vehicle can be powered by solar energy in places without power. In the evenings or rainy days, it is powered by storage battery, and it can be directly powered by alternating current (AC) power supply if available, and the storage battery can be charged full as a backup supply. The proposed system was tested by the alternation of solar irradiance 550 to 700 W/m 2 as solar energy and 500ml ambient temperature water as cooling load. After 160 minutes, the proposal refrigerator can maintain the temperature at 5–8°C, and the coefficient of performance (COP) of NH3 -H2 O absorption refrigeration system is about 0.25. Therefore, this system can be expected to be used in remote areas for refrigeration of food and beverages in outdoor activities in remote and desert areas or long-distance road transportation of food or low temperature refrigeration of vaccine to avoid the deterioration of the food or the vaccines.